Heat and Team Production: Experimental Evidence from Bangladesh - Teevrat Garg; Maulik Jagnani; Elizabeth Lyons (CESifo GmbH, 2024)
Despite the increasing importance of occupations that rely heavily on interpersonal interaction, the impact of heat on team production relative to individual production remains largely unexplored. Heat can affect team and individual production in distinct ways, potentially increasing aggression, thereby complicating team coordination. Conversely, teams may counteract the productivity effects of heat through mutual support strategies, such as sharing tasks, identifying mistakes, or encouragement. We randomly assign programmers to either pair up in teams of two or work independently on a coding task, under either warm (29◦C) or control (24◦C) conditions. Our findings reveal two key insights: (1) Individuals working on coding tasks in warm environments perform comparably to those in control environments. However, teams working in warm conditions significantly underperform relative to teams in control settings. (2) The adverse effects of heat are particularly pronounced in mixed-gender teams and teams with differences in semester-standing, indicating that heat may intensify issues related to coordination and communication within heterogenous teams. Surveys confirm these patterns, with heterogenous teams in warm settings reporting lower partner assessments and a higher desire to switch partners for future tasks.
Keywords: J24; Q54; Q56; 330; team production; heat stress; labor productivity